AppA : a web server for analysis, comparison, and visualization of contact residues and interfacial waters of antibody–antigen structures and models - Nguyen, Minh N. (2019)
The study of contact residues and interfacial waters of antibody–antigen (Ab-Ag) structures could help in understanding the principles of antibody–antigen interactions as well as provide guidance for designing antibodies with improved affinities. Given the rapid pace with which new antibody–antigen structures are deposited in the protein databank (PDB), it is crucial to have computational tools to analyze contact residues and interfacial waters, and investigate them at different levels. In this study, we have developed AppA, a web server that can be used to analyze and compare 3D structures of contact residues and interfacial waters of antibody–antigen complexes. To the best of our knowledge, this is the first web server for antibody–antigen structures equipped with the capability for dissecting the contributions of interfacial water molecules, hydrogen bonds, hydrophobic interactions, van der Waals interactions and ionic interactions at the antibody–antigen interface, and for comparing the structures and conformations of contact residues. Various examples showcase the utility of AppA for such analyses and comparisons that could help in the understanding of antibody–antigen interactions and suggest mutations of contact residues to improve affinities of antibodies.